A MODEL OF ELEMENTARY SCHOOL TEACHERS’ PROFESSIONAL COMPETENCE AS AN EFFORT TO DEVELOP DIGITAL LITERACY - Maman Herman; Deni Mulyadi (Proceeding of International Seminar on Agricultural Conservation and Cultural Heritage, 2025)
This paper is based on the premise that teachers must possess pedagogical competence, personal competence, social competence, and professional competence. These four competencies are holistic and constitute an integrated whole that characterizes professional teachers. The aim of this study is to develop a model of professional competence for elementary school teachers in fostering digital literacy. The research method used is a descriptive method with a literature review approach. The findings indicate that the professional competence of elementary school teachers in building digital literacy is still not optimal. The challenges faced by teachers in implementing professional competence to foster digital literacy include, among others, the limited availability of educational facilities that support the learning process. Efforts made by elementary school teachers to implement professional competence in developing digital literacy include fulfilling the need for adequate educational facilities that are relevant to the demands and conditions of digital era learning. The proposed model of professional competence for teachers in facing the digital era includes: 1) Internet Accessibility; 2) Mobile Devices; 3) Interactive Multimedia; and 4) Digital Learning Platforms.